RESEARCH AND DEVELOPMENT OF INNOVATIONS TO REHABILITATE ARM FUNCTIONALITY IN ELDERLY INDIVIDUALS AND STROKE PATIENTS WITH MUSCLE WEAKNESS - Phunapai, Nittalin; Aramrussameekul, Woraphon; Limboonruang, Teerapath; Sriromreun, Parkpoom; Tawkaew, Sittinun; Srikhongpan, Khajohnsak; Choorat, Pramual (Srinakharinwirot University Journal of Sciences and Technology, 2024)
This research aims to apply the finite element method to design and develop a physical innovation for forearm and hand rehabilitation using a repetitive learning approach. This innovation is intended to restore functionality in patients with cerebrovascular disease and the elderly with muscle weakness in their arms and hands, including improving movement control. It is designed to be self-helping, allowing individuals to regain near-normal arm and hand function. Additionally, it is a prototype for medical technology that is limited and costly, enabling local production and reducing imports. Furthermore, it aims to promote and expand access to effective treatment in Thailand. The innovation focuses on repetitive learning-based physical rehabilitation for managing weak arm muscles. Patients insert their arms into a physical skateboard set to support them and practice moving their arms along a semicircular slide. If a patient’s arm is not strong enough, the device has a function to assist in moving their arm along the slide rail according to the program. The engineering design and analysis results show that the various components of the innovation are structurally sound and suitable for producing a quality product within the specified scope. They can also be used to develop an innovation for restoring arm functionality in patients with muscle weakness due to stroke.